UTILIZATION OF PVA ADHESIVES IN Pinus sp. and Eucalyptus sp. PLYWOOD - Campos, C. I. De; Ferreira, B. S.; Prates, G. A.; Goveia, D.; Valentina, L. V. O. D. (Revista Brasileira de Engenharia de Biossistemas, 2014)
Studies on new adhesives or resins for bonding wood and wood products are being made with the intention of reducing the environmental impact without changing their properties, which is why new PVA (Polyvinyl Acetate) adhesive formulations have been developed. This study tested the use of this adhesive in Eucalyptus sp. and Pinus sp. plywood production with time and temperature of pressing, respectively, 10 minutes and 90°C. The physical tests of density, moisture content and absorption were performed and also the mechanical tests of bending and shear strength in the bondline, all in accordance with relevant standards. There were obtained good results of shear strength in the bondline, which was superior for PVA adhesives compared with plywood produced with urea-formaldehyde and phenol-formaldehyde, whereas the MOE and MOR results were below in both cases.